The Sacred Profane in The Poetry of Salleh Ben Joned - Andrew Hock Soon Ng (Kajian Malaysia, 2012)
Despite Salleh ben Joned's status as an important Malaysian poet, well-versed in two languages, his work has for a long time received critical neglect due to its blasphemous and vulgar nature. This essay is an attempt at reappraising his work in order to appreciate the mechanisms of profanity on which many of his poems are premised; I argue, drawing on the insights of philosopher, Giorgio Agamben, that rather than opposed to the sacred, profanity in Salleh's poem actually enables a regeneration of the former by compelling readers to reassess their faith, and to reconsider the body and the sexual act as sanctified. My view is that what fundamentally discourages readers is not so much the presence of profane terms and near-sacrilegious declarations in the poems, but the offensive tone in them that is only tangentially related to profanity.